DETERMINANTS OF STOCK PRICES AND THE IMPLICATIONS FOR COMPANY VALUE WITH MODERATION OF COMPANY SIZE (EMPIRICAL STUDY ON COMPANIES LISTED IN LQ INDEX 45) - Widya Intan Sari; Jaja Suteja; Mokhamad Anwar (International Journal Multidisciplinary Science, 2025)
This research is aimed at finding out the determinants of share prices, namely Return On Assets (ROA), Net Profit Margin (NPM), Earning Per Share (EPS), Economic Growth, Exchange Rates and Inflation and their implications for company value which is moderated by company size (Study Empirical on Companies Listed on the LQ 45 Index). The method used is panel data regression using the Eviews program. Using a target population of 45 companies and a sample of 22 companies listed on the LQ 45 Index. Return On Assets (ROA), Net Profit Margin (NPM), Earning Per Share (EPS), Economic Growth, Exchange Rates and Inflation affect share prices respectively by 3.98%, 1.685%, 69.46%, 0.896% , 1.1368%, 0.44%. Together, Return On Assets (ROA), Net Profit Margin (NPM), Earning Per Share (EPS), Economic Growth, Exchange Rates and Inflation affect share prices by 72.59%. Of the six variables, Earning Per Share has a more dominant influence on share prices. This research also concluded that share prices have an effect on company value by 79.91%. The influence of share prices on company value through company size is 82.74%, meaning that company size can moderate share prices on company value.